2016
DOI: 10.1016/j.apsb.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Development of a mechanism-based pharmacokinetic/pharmacodynamic model to characterize the thermoregulatory effects of serotonergic drugs in mice

Abstract: We have shown recently that concurrent harmaline, a monoamine oxidase-A inhibitor (MAOI), potentiates serotonin (5-HT) receptor agonist 5-methoxy-N,N-dimethyltryptamine (5-MeO-DMT)-induced hyperthermia. The objective of this study was to develop an integrated pharmacokinetic/pharmacodynamic (PK/PD) model to characterize and predict the thermoregulatory effects of such serotonergic drugs in mice. Physiological thermoregulation was described by a mechanism-based indirect-response model with adaptive feedback con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…To evaluate a possible negative feedback mechanism involved in TG regulation, the indirect response model was tested to include a term to account for an adaptive feedback mechanism . In this model, the feedback function is described as a ratio of TG baseline (Base) to TG levels (i.e., Base/TG) and would affect the total TG production rate ( K in ).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate a possible negative feedback mechanism involved in TG regulation, the indirect response model was tested to include a term to account for an adaptive feedback mechanism . In this model, the feedback function is described as a ratio of TG baseline (Base) to TG levels (i.e., Base/TG) and would affect the total TG production rate ( K in ).…”
Section: Methodsmentioning
confidence: 99%
“…5-MeO-DMT dose dependently reduces locomotor activity, reduces investigatory behaviour but induces forepaw treading, flat-body posture, Straub tail response and hindlimb abduction. This appears to be mainly mediated through 5-HT 1A receptors, with some contribution of 5-HT 2A receptors ( Bedard and Pycock, 1977 ; Castellanos et al, 2020 ; Eide and Tjølsen, 1988 ; Halberstadt, 2016 ; Halberstadt et al, 2008 , 2011 , 2012 ; Jiang et al, 2016b ; Krebs-Thomson et al, 2006 ; Matsumoto et al, 1997 ; Matthews and Smith, 1980 ; Rigdon and Weatherspoon, 1992 ; Smith and Peroutka, 1986 ; Tricklebank et al, 1985 ; Van den Buuse et al, 2011 ). 5-MeO-DMT at high doses inhibits shock-elicited fighting in rats ( Walters et al, 1978 ).…”
Section: Description Of Studies/topicsmentioning
confidence: 99%
“…5-HT 2A receptor-related vasoconstriction is thought to be a main effector site of serotonergic thermoregulation ( Ootsuka et al, 2004 ). Using an experimental drug administration and mathematical pharmacokinetic/pharmacodynamic (PK/PD) model, Jiang et al (2016b) demonstrated that 5-MeO-DMT induces transient hyperthermia in mice. However, another study showed that 3 mg/kg 5-MeO-DMT reduced tail-skin temperature in mice by 1.8°C ( Eide and Tjølsen, 1988 ).…”
Section: Description Of Studies/topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wenli Liu and colleagues use nimodipine as a model drug to demonstrate the potential effects of age and polymorphic form on pharmacokinetics in rats 12 . Xi-ling Jiang and colleagues describe the development of a new mechanism-based PK/PD model to characterize the thermoregulatory effects of serotonergic drugs in mouse models, which may serve as a new framework for the investigation of thermoregulatory or other neuropharmacological effects of serotonergic agents 13 .…”
mentioning
confidence: 99%